Phantom Vibrations and Ringing Syndrome, and its Association with Smartphone Addiction among Department of Anesthesia Technique Students, Al-Kut University College - Mohsin, Talib Saddam; Mubark , Nawras Najah; Al-Hamadiny, Shahad Q. (Journal of Neonatal Surgery, 2025)
Introduction: Phantom vibration syndrome (PVS) and phantom ringing syndrome (PRS) is a false sensation of phone vibration and ringing when it is not. This study aimed to estimate the prevalence of PVS/PRS among Department of Anesthesia Technique Students, Al-Kut University College, Iraq. Methods: Using cross-sectional analytical design, sociodemographic details, information on phantom sensations and phone usage among medical students in Department of Anesthesia Technique Students, Al-Kut University College, Iraq, was obtained. Stratified random sampling strategy was incorporated to achieve a sample size of 1000 students. Also, overuse of phone was assessed using Smartphone Addiction scale - short version (SAS-SV). Results: This study confirms the findings of other national and international research on the experience of smartphone phantom sensations and its relationship to phone usage pattern. The results of the research showed that most of the students in the Department of Anesthesiology are addicted to using smartphones (66%), and their degree of addiction was moderate at 73% and severe at 21%, as the phantom sensation of ringing or vibration was rooted in the students who had a severe addiction to smartphones. Conclusion: This study showed that the severity of addiction to smart phones has a close relationship with phantom sensations. Therefore, other studies are necessary in Iraq to determine the role of PRS/PVS in the accuracy of the sensory health of medical staff working in the hospital in addition to students of medical specialties.